Protective effects of resveratrol against streptozotocin-induced diabetes in rats by modulation of visfatin/sirtuin-1 pathway and glucose transporters - Gencoglu, Hasan; Tuzcu, Mehmet; Hayirli, Armagan; Şahin, Kazım (Taylor & Francis Ltd, 2015)
This experiment was aimed at elucidating the protective effect of resveratrol against diabetes. Forty male Wistar albino rats were allocated into four groups: the control and streptozotocin (STZ)-induced diabetes groups were treated either with placebo (1 ml/kg, i.p.) or resveratrol (20 mg/kg, i.p.) for 8 weeks. Body weight, blood glucose and serum malondialdehyde (MDA) concentrations were monitored. At the end of the experimental period, expression levels of visfatin, sirtuin-1 (SIRT1) and glucose transporters (GLUTs, 2 and 4) were measured in skeletal muscle and pancreas by Western blotting. The resveratrol treatment partially compensated for body weight loss and alleviated hyperglycaemia and returned serum MDA concentrations to the control group levels. Data suggest that supplementation may reduce the severity of diabetes and its complications through suppressing oxidative stress and increasing potential to internalise glucose by extrahepatic tissues.
Keywords: Oxidative stress; polyphenols; preventive medicine; systemic diseases